2020
DOI: 10.1002/14651858.cd013287.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Specialised early intervention teams (extended time) for recent-onset psychosis

Abstract: Specialised early intervention teams (extended time) for recent-onset psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 175 publications
(34 reference statements)
0
23
0
Order By: Relevance
“…In addition, members of the genus Neisseria , including the species Neisseria meningitidis , stimulate the immune system through a variety of mechanisms and invade the neurological nervous system during infection 61 . In this study, we found that the depletion of the genus Roseburia was significantly associated with the local synchronization of spontaneous activity of the right STC and the right MTC, which are related to auditory verbal hallucinations 62 , 63 and thought disturbances 64 in SZ. Dhiman et al 65 reported that Roseburia was associated with good cognitive performance, which may further support our findings.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In addition, members of the genus Neisseria , including the species Neisseria meningitidis , stimulate the immune system through a variety of mechanisms and invade the neurological nervous system during infection 61 . In this study, we found that the depletion of the genus Roseburia was significantly associated with the local synchronization of spontaneous activity of the right STC and the right MTC, which are related to auditory verbal hallucinations 62 , 63 and thought disturbances 64 in SZ. Dhiman et al 65 reported that Roseburia was associated with good cognitive performance, which may further support our findings.…”
Section: Discussionmentioning
confidence: 63%
“…We inferred that the sensory and cognitive impairments might be related to the alteration of ReHo indexes and microbial alpha diversity in SZ. For example, gut microbial alpha diversity in SZ may be associated with visual hallucinations 62 , 67 , and this relationship could be mediated by functional brain activity in the calcarine cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, members of the genus Neisseria, including the species Neisseria meningitidis, stimulate the immune system through a variety of mechanisms and invade the neurological nervous system during infection 53 . In this study, we found that the depletion of the genus Roseburia was signi cantly associated with the local synchronization of spontaneous activity of the right STC and the right MTC, which are related to auditory verbal hallucinations 54,55 and thought disturbances 56 in SZs.…”
Section: Discussionmentioning
confidence: 66%
“…We inferred that the sensory and cognitive impairments may be related to the alteration of ReHo indexes and microbial alpha diversity in SZs. For example, gut microbial alpha diversity in SZs may be associated with visual hallucinations 54,59 , and this relationship could be mediated by functional brain activity in the calcarine cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The younger the patient is, and the more severe the symptoms are, the more important it is to collaborate not just with the individual, but also with the family and other network members ( 15 ). Providing specialized early intervention to treat recent−onset psychosis is likely to have benefits: more people continue with their treatment, and the number of people who recover increases in comparison to treatment as usual (TAU) ( 16 ). Psychoeducation is also suggested to be an important part of the treatment of psychotic disorders ( 17 ).…”
Section: Introductionmentioning
confidence: 99%